Respuesta :
The answer is 10
D= square root (-3-5)^2+ (-5-1)^2
D= square root-8^2+-6^2
D=square root 64 + 36
D=square root 100
D=10
D= square root (-3-5)^2+ (-5-1)^2
D= square root-8^2+-6^2
D=square root 64 + 36
D=square root 100
D=10
Use this formula:
Distance = Square Root ( (X difference)^2 + (Y difference)^2 )
Distance = Square Root (5 - -3)^2 + (1 - -5)^2
Distance = Square Root (64 + 36)
Distance = 10
Distance = Square Root ( (X difference)^2 + (Y difference)^2 )
Distance = Square Root (5 - -3)^2 + (1 - -5)^2
Distance = Square Root (64 + 36)
Distance = 10